Fostering Linguistic Excellence Through Sastranesia: Developing Digital Platform to Enhance Writing Skills and Creativity - Chairunisa, Hera; Wulandari, Ayu Nadira; Arianto, Tomi (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
The integration of digital platforms in education remains underexplored in enhancing creative writing skills in literature programs. This study tried to develop and examines the needs of the press media website, Sastranesia Pers, to accommodate writing creativity of Indonesian Literature students at Medan State University. Using a Research and Development (R&D) approach and the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 100 students enrolled in journalism language courses. The methodology included expert validation of the platform design and content, as well as student feedback through questionnaires and interviews. The findings reveal that the Sastranesia Pers website significantly improved students’ creative writing skills by offering a dynamic, interactive platform for hands-on learning. Students developed proficiency in news writing, editing, and journalistic ethics, bridging theoretical concepts with practical application. Additionally, the website fostered collaborative learning through the formation of a vibrant student press community, which encouraged peer feedback and sustained engagement. Participants reported enhanced confidence in expressing their ideas creatively, while the platform’s accessible design ensured ease of use and high engagement. Furthermore, the integration of digital tools demonstrated an effective approach to addressing challenges in traditional teaching methods, offering real-time feedback and fostering critical thinking. These findings underscore the transformative role of web-based media in language and writing education, with broader implications for integrating digital platforms to support creative and innovative learning.